MENINGKATKAN KEMAMPUAN MOTORIK KASAR MELALUI PENERAPAN BERMAIN BOWLING ANAK USIA 4-5 TAHUN DI PAUD NAZLA ASSYIFA PEKANBARU - Arisanti, Deni Yuni; Indarto, Wusono; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this study was to determine the gross motor skills of children aged 4-5 years in early childhood Nazla Assyifa district handsome Pekanbaru and to know how much gross motor skills through play bowling. Researchers conducted action research through observation of the child's gross motor skills by developing indicators based on the regulation number 58 of 2009. From the results of research and discussion, we concluded that gross motor skills of children aged 4-5 years in early childhood Nazla Assyifa Pekanbaru, the results of research 2 cycles improves significantly compared with the pre-cycle average of 43.33%. In the first cycle of gross motor skills children have started to experience an increase in the average 57.96%, which is continued in the next cycle gross motor skills by an average of 84.63% with criteria developed according to expectations (BSH). In the first cycle of the child's activity on average by 50.06% Less criteria (K), while the second cycle of the child's activity has increased on average by 76.13% with criteria Good (B). In the first cycle of teachers on average by 55.55% Less criteria (K), while the second cycle of teachers has increased by an average of 85.18% with criteria Good (B). From these results it can be concluded that the bowling gave a positive response to child childhood Nazla Assyifa District Charming Pekanbaru. can improve gross motor skills with the percentage of 84.63%.Key words: Gross motor skills, play Bowling